2014
DOI: 10.2478/s11756-013-0315-y
|View full text |Cite
|
Sign up to set email alerts
|

Hoverfly (Diptera: Syrphidae) community of a cultivated arable field and the adjacent hedgerow near Debrecen, Hungary

Abstract: A hoverfly (Syrphidae) community was investigated in a cultivated wheat field and the adjacent hedgerow near Debrecen (Hungary). We monitored the change of species richness and abundance of hoverflies along three transects in the hedgerow and in the wheat field in different distances (10 m, 20 m) from the hedgerow. The effect of sampling methods on the number of hoverfly species and individuals was analyzed. Two sampling methods were used to catch hoverflies: netting and pan traps. The whole sampling period wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Studies of Syrphidae in Australian ecosystems (including ours) have the lowest species richness of any such communities studied to date. The next lowest Syrphidae diversity was reported in Hungary, where 22 species were recorded in arable ecosystems (Földesi & Kovács‐Hostyánszki 2014). In Canada, previous studies identified 28 and 29 species in Quebec and Ontario, respectively (Blades & Marshall 1994; Moisan‐DeSerres et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of Syrphidae in Australian ecosystems (including ours) have the lowest species richness of any such communities studied to date. The next lowest Syrphidae diversity was reported in Hungary, where 22 species were recorded in arable ecosystems (Földesi & Kovács‐Hostyánszki 2014). In Canada, previous studies identified 28 and 29 species in Quebec and Ontario, respectively (Blades & Marshall 1994; Moisan‐DeSerres et al .…”
Section: Discussionmentioning
confidence: 99%
“…Syrphids have high floral constancy, and some can be efficient pollinators (Goulson & Wright 1998; Ssymank et al . 2008; Földesi & Kovács‐Hostyánszki 2014), potentially transferring as much pollen as honeybees (Rader et al . 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on field-level studies and modeling efforts, windbreaks, hedgerows, and alley cropping systems can provide pollinator habitat close to crops and at a scale that can benefit foraging [22,29,30,53,103,104,[117][118][119][120]149]. For instance, Morandin and Kremen [22] observed higher native bee and honey bee numbers in fields adjacent to hedgerows than in fields adjacent to control edges.…”
Section: Site Connectivitymentioning
confidence: 99%